Development and Activity of the Institute of Geography, Kazimierz Wielki University in 1995-2016 (Geography and Tourism, 2017)
The Institute of Geography of Kazimierz Wielki University, founded in 1996, initially as the Chair of Geography, is the youngest geography research and didactic unit in Poland. The Institute runs two-cycle studies in two fields: Geography as well as Tourism and Recreation (bachelor’s and complementary master’s studies), and two engineering courses: Inland Waterways Revitalization and Crisis Management in the Natural Environment. After twenty years of student education, graduates of the Institute of Geography have an impact on the natural environment management on a local and national scale, by taking positions at various levels, including managerial positions in local authorities’ units, institutions connected with environmental protection as well as private enterprises. The academic research of the Institute of Geography focuses on issues related to physical geography and socio-economic geography as well as tourism and recreation. Currently, the most important topics are: the impact of human activity on fluvial systems, problems related to revitalization of waterways and riverside areas, geodiversity of selected areas in Poland, contemporary socio-economic processes in Poland and other transition countries, tourism development and economics. The scientific research and expert activities of the Institute’s employees in the indicated fields include research works both worldwide, nationwide, as well as on a local scale – the Kujavian-Pomeranian Voivodeship and the city of Bydgoszcz. The research is carried out within the framework of cooperation with Polish and foreign academic institutions, as well as in the scope of implementation works with local authorities’ units, landscape parks and private enterprises. Since 2013, the Institute of Geography has published the “Geography and Tourism” academic journal, which popularizes the results of theoretical and empirical research in the fields of geography and tourism.